1994
DOI: 10.1002/tcm.1770140602
|View full text |Cite
|
Sign up to set email alerts
|

Human carcinogenic risk assessment based on hormonal effects in a carcinogenicity study in rats with the antifungal agent, fluconazole

Abstract: Fluconazole is an orally active bis-triazole antifungal agent that acts by selective inhibition of lanosterol 14 alpha-demethylase, a key enzyme for maintenance of the fungal cell wall. It is not genotoxic. In a 2 year carcinogenicity study in Sprague-Dawley rats, fluconazole decreased mammary fibroadenomas in females and adrenal pheochromocytomas in males, and increased hepatic adenomas in males. The pattern of these changes is explicable in terms of a hormonal imbalance, corroborated in other studies with fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although studies indicate that FCZ can cause tumors, this is extremely unlikely to occur in humans. 75 In recent work, Tamura et al 76 investigated liver hypertrophy and tumor development in mice induced by FCZ and two other triazoles. It was found that FCZ could induce hepatic hypertrophy and the development of tumors in the liver.…”
Section: Carcinogenicitymentioning
confidence: 99%
“…Although studies indicate that FCZ can cause tumors, this is extremely unlikely to occur in humans. 75 In recent work, Tamura et al 76 investigated liver hypertrophy and tumor development in mice induced by FCZ and two other triazoles. It was found that FCZ could induce hepatic hypertrophy and the development of tumors in the liver.…”
Section: Carcinogenicitymentioning
confidence: 99%
“…It was introduced in early 1990 as prophylactic antifungal after bone marrow transplantation 2 . Fluconazole acts by selective inhibition of lanosterol 14-alphademethylase, a key enzyme for maintenance of the fungal cell wall 3 . It has a favourable pharmacokinetic profile that includes a long serum half-lifetime, which makes once-daily administration possible, more consistent absorption from the gastrointestinal tract than that of ketoconazole, excellent penetration into the cerebrospinal fluid, and elimination predominantly by a renal mechanism 4 .…”
Section: Introductionmentioning
confidence: 99%